Next Generation Sequencing of Bee Gut Microbiota in Urban and Rural Environments - Rustemoglu, Mustafa (Mdpi, 2023)
The gut microbiota plays a vital role in the physiological and behavioral processes of organisms, thereby influencing the quality of life of their host. Investigating the microbial diversity of the gut microbiota of Apis mellifera, the ecological organizer, may provide key insights into the ecological and health-related factors affecting host populations. This study aims to investigate the comparative gut microbiota of forager A. mellifera collected from both rural and urban environments in each of the four provinces located in southeastern Turkiye by employing Next Generation Sequencing (NGS) technology, specifically amplicon metagenome sequencing targeting the V3-V4 region of the 16S rRNA gene. In general, the urban samples possessed a higher level of gut microbial diversity when compared with the rural samples. Interestingly, the rural samples, in addition to the majority of previously reported core microbiota members, contained human pathogens such as Salmonella enterica, Klebsiella pneumoniae, Escherichia coli, and Streptococcus pyogenes. Moreover, this study is the first to report the predominant existence of Enterococcus wangshanyuanii, Alkalihalobacillus halodurans, and Vitreoscilla sp. in several samples. This study contributes to the idea that urban apiculture practices can alter bacteria residing in the digestive tracts and discusses possible effects of potential infestation of A. mellifera by human-pathogenic bacteria on different aspects of life traits.
Keywords: Apis mellifera; 16s metabarcoding; urban beekeeping; microbiota; human pathogens; Turkiye